RELATIONSHIP OF SERVICE QUALITY DIMENSIONS WITH SERVICE SATISFACTION ANTENATAL CARE - Tri Shinta Maesaroh; Elisa Ulfiana; Aulia Octaviana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
According to data and health information from the Grobogan District Service, Puskesmas Godong II is one of the Puskesmas with the coverage of Antenatal Care lowest. In 2016 the coverage of K1 was 100%, K4 was 94.42% and in 2017 KI was 100%, K4 was 93.37%. The gap that occurs between K1 and K4 is due to patients feeling dissatisfied with the services provided so that patients do not make repeat visits and have an impact on the decline of in coverage Antenatal Care. The purpose of this study to determine the relationship of the dimensions of quality of service reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy), tangible (physical evidence to the satisfaction of service Antenatal Care.The study was conducted in Puskesmas Godong II with a sample of 55 pregnant women. Sampling technique with purposive sampling. The instrument used was a structured questionnaire. The data analysis used Chi-Square.The results showed the dimensions of service quality, reliability (reliability), responsiveness (responsiveness), assurance (guarantee), empathy ( empathy), tangible (physical evidence), and satisfaction, many respondents have a good perception P-value service quality 0.001, reliability 0.002, responsiveness (responsiveness) 0.010, assurance (guarantee) 0.005, empathy (empathy) 0.009, tangible (physical evidence) 0.000. These results indicate a relationship between the dimensions of service quality reliability (reliability), responsiveness endless (responsiveness), assurance (assurance), empathy (empathy), tangible (physical evidence) with satisfaction service Antenatal Care.It is hoped that midwives can work professionally and improve the quality of work, especially accuracy, responsiveness, skills, and friendliness, and for health centers to be able to provide good facilities and infrastructure, especially clean rooms and environments as well as complete room attributes.